Avenir® vs. AxiumTM Coils for the Treatment of Intracranial Aneurysms: Results of a Multicenter Randomized Controlled Trial With Short-Term Follow-Up - Li, Wei; Ye, Ming; Cimpoca, Alexandru; Henkes, Hans; Wang, Honglei; Xu, Xiang; Gu, Yuxiang; Shi, Huaizhang; Ji, Hongming; Wang, Feng; Zhao, Yuanli; Guo, Geng; et al. (Frontiers in Neurology, 2022)
Purpose: Endovascular coil occlusion is a successful and rapidly evolving treatment for patients with intracranial aneurysms. The aim of this study was to compare the safety and efficacy of two passive mechanically detachable coil systems, Avenir and Axium, for the treatment of intracranial aneurysms. Methods: A prospective, multicenter, randomized controlled study was carried out at 10 medical centers from March 2018 to December 2019. Consecutive patients with intracranial aneurysms were randomly assigned to receive either the Avenir (Avenir group) or Axium (Axium group) mechanically detachable coil systems. The two groups were compared for efficacy and safety. Results: A total of 162 and 161 patients were enrolled in the Avenir and Axium groups, respectively. At 6-months follow-up, the aneurysm occlusion rate was 94.66% for the Avenir group and 96.95% for the Axium group (p>0.05). Surgical complications occurred in 27 subjects in the Avenir group and 22 in the Axium group (p>0.05). There was no difference between the study groups in terms of the clinical condition (modified Rankin Scale) or the degree of aneurysm occlusion (DSA, Raymond Roy classification) at the end of the 6-month follow-up period. Short-term DSA at 6 months showed complete aneurysm occlusion in 84% of Avenir patients and in 86% of Axium patients. Conclusion: Avenir and Axium coils showed no significant difference in efficacy and safety for the treatment of intracranial aneurysms in short-term follow-up.